Baseline risk factors determine lack of biochemical response after SVR in chronic hepatitis C patients treated with DAAs. (25th July 2019) - Tacke, Frank; Boeker, Klaus H.W.; Klinker, Hartwig; Heyne, Renate; Buggisch, Peter; Pathil, Anita; Wiegand, Johannes; Cornberg, Markus; Lange, Christian; Berg, Thomas; Zeuzem, Stefan; Mauss, Stefan
Abstract: Background and Aims: Liver function tests (alanine aminotransferase, ALT; gamma‐glutamyltransferase, GGT) not always normalize after elimination of hepatitis C virus (HCV) by direct acting antivirals (DAAs), possibly indicating concomitant non‐viral liver diseases. We analysed factors determining the biochemical response (normalized ALT/GGT) of DAA therapy in a large real‐world cohort. Method: The German Hepatitis C‐Registry is a national multicenter registry study. Normal ALT was defined ≤35 U/L (female) and ≤50 U/L (male) or, according to AASLD, ≤19 U/L (female) and ≤30 U/L (male), normal GGT ≤40 U/L (female) and ≤60 U/L (male). Results: At baseline, ALT was elevated in 3705/4946 (74.9%), ALT (AASLD) in 4669/4946 (94.4%) and GGT in 3018/4906 (61.5%). In this study, 97% of patients achieved SVR12. At week 12 after end of therapy, ALT was elevated in 451/4946 (9.1%), ALT according to AASLD in 1906/4946 (38.5%) and GGT in 863/4879 (17.7%). Persistently elevated ALT after DAA therapy was independently associated with high body mass index (BMI), age <70 years, liver cirrhosis, diabetes, alcohol consumption and not achieving SVR12. Using the stricter AASLD criteria, opioid substitution and male sex were additional predictors. Higher GGT at week 12 was associated with high BMI, age >70 years, liver cirrhosis, diabetes, alcohol consumption, opioid substitution and non‐SVR. Importantly, persistently elevated liver tests after treatment, particularly GGT, were associated with hepatic decompensation and mortality during 4‐years follow‐up. Conclusion: Risk factors at baseline (obesity, diabetes, liver cirrhosis, alcohol consumption) are independently associated with persistently elevated liver function tests after SVR, indicating that these patients warrant further hepatological follow‐up. Clinical trial registration: German Clinical Trials Register (DRKS; ID DRKS00009717). Abstract : See Editorial on Page 509